Analisis Kritis terhadap Keterlibatan Tentara Nasional Indonesia dalam Pemberantasan Tindak Pidana Terorisme - La Ode Muhammad Ismail; Alfian Silondae; Fuad Nur (Jurnal Ilmu Sosial dan Humaniora, 2026)
Law Number 5 of 2018 on the Eradication of Terrorism Crimes provides the legal basis for the involvement of the Indonesian National Armed Forces (Tentara Nasional Indonesia/TNI) in counterterrorism efforts as a response to the escalating threat of terrorism. The expansion of TNI’s authority raises significant juridical concerns, particularly with regard to the principles of due process of law and the protection of human rights. This study employs a normative juridical method using statutory, doctrinal, and academic literature approaches relevant to criminal law policy and criminal justice policy. The findings indicate that TNI involvement through military operations other than war (MOOTW) has the potential to generate repressive actions that are inconsistent with the paradigm of criminal law enforcement. Such risks include the possibility of extrajudicial killings and violations of fundamental principles under the Indonesian Criminal Procedure Code, such as the presumption of innocence and the right to a fair trial. Therefore, the involvement of TNI in counterterrorism efforts should be limited, auxiliary to the Police, and implemented based on political decisions of the state while ensuring the protection of human rights and legal certainty.